The Contribution of Public Health Technicians to Epidemic Response and Community Health Safety - Yahya Hifth Allah Hakami,; Hassan Mohammad Tohary,; sirajfahad Mohammed hakami,; ziyad mouse hakami,; Mousa Omar Hakami,; Othman Musawi Hakami,; Ibrahim Mohammed Hakami,; Ahmad Ibrahim hadi Hakami,; Ahmed Mohammed Qaba Ahmed,; Awagi Msawa Mohammed Hakami, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Although community health workers (CHWs) are crucial to resource-limited health systems, little is known about their pandemic preparedness role. Community Health Workers (CHWs) enhanced access to health services and products, communicated health concepts with cultural sensitivity, and alleviated strain on formal healthcare systems prior to pandemics. Community Health Workers (CHWs) informed and organized communities, enhanced surveillance systems, and mitigated health service deficiencies during pandemics. Community Health Workers (CHWs) have demonstrated proficiency in these roles and previous initiatives; therefore, we advocate for their increased utilization in pandemic preparedness. Practical strategies include training and employing Community Health Workers (CHWs) to disseminate One Health information to vulnerable populations before outbreaks, consolidating them into a reserve health corps for public health emergencies, and formalizing agreements and strategies to facilitate CHW early involvement in response initiatives. Community Health Workers (CHWs) already contribute to pandemic preparedness, thus expanding their duties and responsibilities is a sensible way to boost pandemic and community resilience.